Dampak Sosial Ekonomi Pabrik Karet PT Karya Sejati bagi Masyarakat Murung Keramat - Rochgiyanti Rochgiyanti; Arisandi Arisandi; Heri Susanto; Fathurrahman Fathurrahman; Rhoma Dwi Aria Yuliantri (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The existence of a factory in an area has an impact, including PT. Karya Sejati, which operates in the rubber sector, has had an impact on the people of the Murung Keramat Village. The purpose of this study was to determine the positive socio-economic impact of the PT. True Work. The method used in this research uses descriptive qualitative. Data obtained through observation, interviews, and various literature. Data analysis refers to Miles and Huberman s technical data analysis. The results of his research show that the rubber factory PT. Karya Sejati has a positive socio-economic impact on society. These impacts includeabsorption of labor thereby reducing the number of unemployed and improving the economy of the surrounding community.